The power of controversy: examining the role of conflict on consumer attitudes, evaluations, and purchase intentions - Steidle, Bianca (2022)
Today’s consumers want brands to engage in socio political topics. However, this can be offensive and cause personal conflict. This work hypothesizes that when consumers think about these conflicts, their evaluation, and intentions towards brands that take a stand differ. Additionally, it examines how consumers’ reactions to a brand’s stand on a controversial vs. non-controversial topic influence conflict, attitudes, and purchase intention. Two main experiments were conducted. The results didn’t show a difference when consumers either did or didn’t think about conflict. Nonetheless, the controversial brand’s engagement increased conflict perception. This negatively impacted attitudes that were positively linked to purchase intentions.